2021
DOI: 10.9734/arrb/2021/v36i730394
|View full text |Cite
|
Sign up to set email alerts
|

Haematological and Biochemical Profile of Wistar Rats Exposed to Chloroform Stem Extract of Portulaca oleracea Linn. (Purslane)

Abstract: Portulaca oleracea Linn. has a history of extensive use as a medicinal plant and is a component of the Nigerian ethnomedical pharmacopoeia. Although several studies have been carried out exclusively on the leaves to ascertain the physiological effect, there seems to be dearth of literature on the physiological effect of the stem. This study which was designed to fill this gap investigated the sub-chronic effect of oral administration of chloroform stem extract of P.oleracea (CSEPO) on haematological parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…The same observations resulted from other similar studies on mice and rats, where no significant changes in the body weight and hematological parameter values were observed after the administration of CP-based formulations at a 5 mg/kg body weight and after 6 days [11,12,27]. LY% was slightly higher than the normal limits in rats; however, the total LYM count was in the normal range [43][44][45][46]. No lymphocytopenia (low level of LYM) was observed after CP or CP-based formulation treatments.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The same observations resulted from other similar studies on mice and rats, where no significant changes in the body weight and hematological parameter values were observed after the administration of CP-based formulations at a 5 mg/kg body weight and after 6 days [11,12,27]. LY% was slightly higher than the normal limits in rats; however, the total LYM count was in the normal range [43][44][45][46]. No lymphocytopenia (low level of LYM) was observed after CP or CP-based formulation treatments.…”
Section: Discussionsupporting
confidence: 85%
“…A decrease in the iron-related hematological parameters was observed for the γ-CD/CP-treated group. The RBC and HGB values were only 7.1 × 10 12 /L and 12.3 g/dL (slightly lower than the normal values of 5.3-10 × 10 12 /L and 14-18 g/dL, respectively) [43][44][45][46], whereas for the γ-CD/CP binary and γ-CD/Rv/CP ternary complexes they were 7.9-8.4 × 10 12 /L and 13.7-14.7 g/dL, respectively (lower values for the binary complex). These differences occurred in healthy rats due to some kidney problems that were more affected by the treatment with the CP solution (anemia), less affected after treatment with the γ-CD/CP binary complex, and almost not affected by using the antioxidant-protected γ-CD/Rv/CP ternary complex.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The cytotoxic impact of ACR may trigger ROS formation, leading to cytotoxic and genotoxic consequences through alterations in the cellular redox state (Gao et al., 2023 ). Research has shown that the bioactive constituents present in certain plants possess the capacity to alleviate oxidative stress (Alaee et al., 2023 ; Bolouki et al., 2020 ; Mbiba Hassanu et al., 2022 ; Mohammadi et al., 2023 ; Obinna & Agu, 2023 ; Ojatula, 2021 ; Oyetunji et al., 2021 ; Yaghutian Nezhad et al., 2021 ). Hence, it appears that antioxidant molecules might aid in mitigating the deleterious effects of this compound.…”
Section: Introductionmentioning
confidence: 99%
“…13 Many herbal plants contain antioxidant properties which can preserve reproductive tissues against different toxicity. [14][15][16][17][18][19][20] Resveratrol (also known as 3,5,4'-trihydroxy-trans-stilbene) is a natural phytoalexin. 21,22 There are at least 27 plant species that contain this compound.…”
Section: Introductionmentioning
confidence: 99%